Opportunities and threats of digital transformation for village shops: Coronavirus pandemic as a catalyst? - Eberhardt, Winfried; Küpper, Patrick; Seel, Matthias (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
The Corona crisis offers the window of opportunity to accelerate digitization processes in food retailing. Village shops and rural consumers are traditionally not considered to be digitization pioneers. The research question is: How do the Corona pandemic and digital transformation affect village shops and their customers? For answering this question, we present findings of a two-wave household survey in six case study areas as well as results from qualitative interviews with operators of twelve village shops and ten experts. The experiences in the Corona crisis demonstrate the high resilience of the village shops due to increased local demand and flexible adaptation strategies. The contribution of digitization remains limited, even though this transformation is taking place evolutionary in the village shops using trial and error. One danger for village shops is that consumers tend to buy more online due to Corona. Purchasing power outflows in online retail make shop closings more likely, which in turn leads to more online shopping as a coping strategy for consumers when there is no local supply. Thus, we are adding a critical perspective to the discussion on smart villages by not only emphasizing the new digital possibilities, but also by clarifying the risks.